Eksplorasi Komitmen Organisasi Karyawan pada Amal Usaha Pendidikan Muhammadiyah: Studi Indigenous Psychology - Muhammad Fath Mashuri; Ahmad Sulaiman (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Individuals who choose to work in Muhammadiyah’s philanthropy movement in education should be obliged to serve and support the organization. This, of course, cannot be separated from the degree of commitment of each individual. This study aims to explore the work commitment of individuals who work in Muhammadiyah educational charities using the indigenous psychology approach in which it is possible to construct the concept of commitment through a bottom-up approach. Respondents were teachers/ employees at Muhammadiyah’s philanthropy movement in education. The number of respondents was 169 people from several provinces in Indonesia. The results show that several factors make employees/ teachers/ lecturers at Muhammadiyah Business Charity in the field of education commit to their organization, namel: (1) organizational factors; (2) intrapersonal factors; (3) interpersonal factor; and (4) religiosity factors.